Biochemical and histological impact on sub-lethal concentration of Glyphosate on Channa punctataus (Bloch) fish (International Journal of Food and Nutritional Sciences, 2022)
Herbicides are mainly used to protect the crops, and plays vital role in management practice for the benefit of agricultural productivity,. It take pivotal part in agricultural field to kill the pests in order to produce the highly verities of crop. Glyphosate in the surrounding, has payed a lot of attention towards the sub-lethal effects of chronic exposures on Non- target organisms. In present work Channa punctatus was used as non target animal. The fishes were acclimatized near about 10 days, dead and infected fished were removed immediately. The sub lethal concentration, 24 hours, 96 hours, 7 days, 15 days and 30 days respectively was studied during research work. The work showed, gradual decline of protein as well as histopathylogical change in gill.